Co-adaptation of ball reception to the serve constrains outcomes in elite competitive volleyball. Issue 2 (April 2018) - Paulo, Ana; Davids, Keith; Araújo, Duarte
How impactful is volleyball's "serve-reception game"? Its efficacy has been found to discriminate between winning and losing a match. But how does reception become (in)effective? Based on the theoretical rationale of ecological dynamics, we hypothesized that skilled receivers in volleyball would not display ready-made responses, but rather would co-adapt action modes during serve-reception to deal with the specific, emergent constraints of serve to achieve task goals. In order to examine this issue, we investigated whether the co-adaptation of serve and reception action modes was a significant predictor of set outcome in elite volleyball performance (win or loss), analyzing the first and last sets of the 2014 World League Finals matches (897 game-sequences). The power-jump and jump-float were the serving modes observed and the overhand, underhand-lateral, and underhand-frontal passes were the reception modes categorized. We found that the co-adaptation of serve and reception action modes predicted set outcome in the final set of a match. Receiving the jump-float serve with an overhand pass or underhand-lateral pass increased the odds of winning the final set by 200%. Results suggested that, at an expert level, mastering the overhand pass and the underhand-lateral pass gives teams a competitive edge. Receivers showing flexibility in action mode selection improved a team's odds of successfully winning the final set of a match.